Design of a peptide inhibitor that blocks the cell fusion mediated by glycoprotein 41 of human immunodeficiency virus type 1 - Jin, BS; Ryu, JR; Ahn, K; Yu, YG (MARY ANN LIEBERT INC PUBL, 2000)
Fusion between the envelope of HIV and the plasma membrane of target cells is mediated by gp41, the envelope glycoprotein of HIV. Peptides derived from the membrane-proximal helical motif of the extracellular domain of gp41 effectively inhibit the infection of HIV, and their inhibitory activities are known to be correlated with the helical propensity of the peptides. We have designed small peptides that can form a stable alpha helix and thereby inhibit gp120/41-mediated cell fusion. A 19-mer peptide from the membrane-proximal helical motif of gp41 had no secondary structure in solution, and failed to block gp41-mediated cell fusion. When amino acids with low helical propensity were substituted, and helix-capping sequences were introduced at both ends of the peptides, the modified peptides formed a stable helical structure. They also bound to the coiled-coil motif of gp41 presented at the C terminus of thioredoxin and blocked the cell fusion mediated by gp120/41. These results implied that such modification was enough to change a short peptide derived from gp41 into a potent inhibitor against the infection of HIV.
Keywords: ZIPPER-LIKE DOMAIN; ENVELOPE GLYCOPROTEIN; COILED-COIL; HIV-1 GP41; HELIX; PROTEIN; CONFORMATION; STABILITY; PROPENSITY; INFECTION